Positive affect through interactions in meetings: The role of proactive and supportive statements - Schneider, Kurt; Klünder, Jil; Kortum, Fabian; Handke, Lisa; Straube, Julia; Kauffeld, Simone (Journal of Systems and Software, 2018)
Software projects are dominated by meetings. For participants, not all meetings are useful and enjoyable. However, interaction within a meeting has an impact on individual and group affects. Group affect influences team performance and project success. Despite frequent yet vague dissatisfaction with some meetings, many software engineers are not aware of the crucial importance of their behavior in those meetings. This can set the tone for the entire project. By influencing group affect, meeting interaction influences success without participants even noticing. Due to this lack of awareness, it depends on good or bad luck whether software teams will adopt a promising meeting style. In a study of 32 student projects with 155 participants, we coded fine-grained interaction elements during the first internal meeting of each team. The analysis of resulting codes showed that constructive remarks had a positive impact on positive group affect tone (PGAT). However, this effect was only observed when constructive remarks were followed by supportive utterances. We were able to show a complete mediation of this statistically significant effect. Seemingly subtle behavior patterns influence group affect. Software projects could significantly benefit from supportive meeting behavior. We propose practical interventions to improve meeting quality.
CRIS-Team Scopus Importer:2023-09-18
Keywords: Empirical study; Positive group affect tone (PGAT); Proactive and supportive statements; Statistical analysis of mediation and sequence